2023
DOI: 10.1186/s12962-023-00425-z
|View full text |Cite
|
Sign up to set email alerts
|

Essential emergency and critical care as a health system response to critical illness and the COVID19 pandemic: what does it cost?

Abstract: Essential Emergency and Critical Care (EECC) is a novel approach to the care of critically ill patients, focusing on first-tier, effective, low-cost, life-saving care and designed to be feasible even in low-resourced and low-staffed settings. This is distinct from advanced critical care, usually conducted in ICUs with specialised staff, facilities and technologies. This paper estimates the incremental cost of EECC and advanced critical care for the planning of care for critically ill patients in Tanzania and K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Scaling up advanced critical care is costly(34) and complex and might not be effective (35) or cost-effective in the short term for countries with scarce resources such as Tanzania(36). A study done in Tanzania and Kenya during the COVID-19 pandemic, showed the cost of advanced critical care to be 7 to 9 times higher than that of EECC (11). Focusing on improving readiness for EECC before scaling up advanced critical care is likely to yield greater bene ts and reduce the need for advanced critical care, thus allowing it to be available for the patients where EECC is not enough.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scaling up advanced critical care is costly(34) and complex and might not be effective (35) or cost-effective in the short term for countries with scarce resources such as Tanzania(36). A study done in Tanzania and Kenya during the COVID-19 pandemic, showed the cost of advanced critical care to be 7 to 9 times higher than that of EECC (11). Focusing on improving readiness for EECC before scaling up advanced critical care is likely to yield greater bene ts and reduce the need for advanced critical care, thus allowing it to be available for the patients where EECC is not enough.…”
Section: Discussionmentioning
confidence: 99%
“…Resource requirement lists for EECC (66 items -Supplementary Table 1, Additional File 1) and advanced critical care (161 items -Supplementary Table 2, Additional File 1) developed in previous studies were used for de ning hospital-availability and ward-readiness (10,11). The lists group resources in the eight categories of infrastructure, human resources, equipment, consumables, drugs, training, guidelines, routines with an additional ninth category of support systems for advanced critical care, (care beyond the critical care location such as laboratory tests and imaging).…”
Section: De Nitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact the unmet needs of care for most critically ill patients [5][6][7][8][9] can be provided outside ICUs. 4,11,13,38 The recently defined Essential Emergency and Critical Care (EECC) includes 40 foundational interventions selected for clinical effectiveness and feasibility in all hospital settings, such as triage, airway protection and oxygen therapy. 3,12 EECC aligns with the WHO's Fair Priorities framework to maximize the population impact of care interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Such critical care interventions are needed wherever a critically ill patient is located. 1,2 Although many effective critical care interventions are low-cost and feasible throughout hospitals 3,4 there is alarming evidence from different settings that they are frequently not provided. [5][6][7][8][9] Improving critical care has the potential to increase survival across medical disciplines.…”
Section: Introductionmentioning
confidence: 99%